Pengaruh Perceived Organizational Support terhadap Organizational Citizenship Behavior dengan Work Engagement sebagai Variabel Pemediasi - Indri Wahyuni; Sulastri Sulastri (Universitas Negeri Padang, 2020)
Purpose - This research analyzed: (1) The influence of Perceived organizational suport on work engagement at PT Padang Intermedia Pers (2) The influence of work engagement on organizational citizenship behavior at PT Padang Intermedia Pers (3) The influence of perceived organizational support on organizational citizenship behavior at PT Padang Intermedia Pers (4) The influence of perceived organizational support on organizational citizenship behavior through work engagement at PT Padang Intermedia Pers.Methodology- This research is causal research. The populations were all employee in the PT Padang Intermedia Pers, amounting to 102 people. The number of samples was determined using cluster propotional sampling technique. This research analyzed using path analysis with SmartPLS3.Finding- Regarding the partial mediation model proposed, the data confirm the relationship set out in the hypothesis. This research found that (1) Perceived organizational support has positive and significant effect work engagement in PT Padang Intermedia Pers (2) Work engagement has a positive and significant effect on organizational citizenship behavior in PT Padang Intermedia Pers (3) Perceived organizational support has a positive and significant effect on organizational citizenship behavior in PT Padang Intermedia Pers (4) Work engagement mediates the relationship between perceived organizational support and organizational citizenship behavior.